Expansion of Umbilical Cord Blood Aldehyde Dehydrogenase Expressing Cells Generates Myeloid Progenitor Cells that Stimulate Limb Revascularization. (15th June 2017) - Putman, David M.; Cooper, Tyler T.; Sherman, Stephen E.; Seneviratne, Ayesh K.; Hewitt, Mark; Bell, Gillian I.; Hess, David A.
Abstract: Uncompromised by chronic disease-related comorbidities, human umbilical cord blood (UCB) progenitor cells with high aldehyde dehydrogenase activity (ALDH hi cells) stimulate blood vessel regeneration after intra-muscular transplantation. However, implementation of cellular therapies using UCB ALDH hi cells for critical limb ischemia, the most severe form of severe peripheral artery disease, is limited by the rarity (<0.5%) of these cells. Our goal was to generate a clinically-translatable, allogeneic cell population for vessel regenerative therapies, via ex vivo expansion of UCB ALDH hi cells without loss of pro-angiogenic potency. Purified UCB ALDH hi cells were expanded >18-fold over 6-days under serum-free conditions. Consistent with the concept that ALDH-activity is decreased as progenitor cells differentiate, only 15.1% ± 1.3% of progeny maintained high ALDH-activity after culture. However, compared to fresh UCB cells, expansion increased the total number of ALDH hi cells (2.7-fold), CD34 + /CD133 + cells (2.8-fold), and hematopoietic colony forming cells (7.7-fold). Remarkably, injection of expanded progeny accelerated recovery of perfusion and improved limb usage in immunodeficient mice with femoral artery ligation-induced limb ischemia. At 7 or 28 days post-transplantation, mice transplanted with expanded ALDH hi cells showed augmented endothelial cell proliferation and increased capillary density compared to controls. Expanded cells maintained pro-angiogenic mRNA expression and secreted angiogenesis-associated growth factors, chemokines, and matrix modifying proteins. Coculture with expanded cells augmented human microvascular endothelial cell survival and tubule formation under serum-starved, growth factor-reduced conditions. Expanded UCB-derived ALDH hi cells represent an alternative to autologous bone marrow as an accessible source of pro-angiogenic hematopoietic progenitor cells for the refinement of vascular regeneration-inductive therapies. Abstract : Human umbilical cord blood cells with high aldehyde dehydrogenase-activity retain vascular regenerative capacity after ex vivo expansion. After 6 days expansion under clinically applicable (serum-free, xeno-free) conditions ALDH hi cells gradually lose primitive hematopoietic progenitor phenotype but retain potent paracrine revascularization function after intramuscular transplantation into NOD/SCID mice with femoral artery ligation induced limb ischemia.